Pengaruh Waktu Penyimpanan Larutan Oral Nutraceutical Ekstrak Bunga Delima Merah (Punica Granatum L.) Terhadap Perubahan Hambatan Pertumbuhan Staphylococcus Aureus (In Vitro) - Utomo, Primideta Putra; , drg. Mahmud Kholifa, MDSc (2017)
Staphylococcocus aureus is one of bacteria that causing periodontal abscess. In treatment, it is required to have a substance that has antibacterial activity. In the present era, the use of chemicals assessed as having side effects in the long term of using, so it is necessary to have natural alternative substance, practical and safe to be consumed as the red pomegranate flowers made in nutraceutical oral solution form. Red pomegranate flower's (Punica granatum L.) contains antibacterial such as flavonoids, alkaloids, saponins, phenolic, proantosianin, and tannins. utraceutical oral that had been made is necessary to be stored. Factors influencing the changes in bacterial growth inhibition toward the storage time is temperature, light and humidity. The objective of this study was to determine the effect of storage time of red pomegranate flower's (Punica granatum L.) extract nutraceutical oral solution toward the changes in growth inhibition of Staphylococcus aureus.This type of research was an experimental study with post test only control group design. The method used by measuring the clear zone inhibitory diameter on the petri dish with the addition of an nutraceutical oral solution of red pomegranate flower's extract which has not been stored, after 7 days of storage, after 14 days of storage, after 21 days of storage, and after 28 days of storage.The results showed inhibition zone diameter on each treatment. One way Anova test results showed the value of p = 0.000 (p <0.05). Post Hoc LSD test showed significant p value <0.05 after 28 days of storage, so it can be concluded that the effect of storage time nutraceutical oral solution of red pomegranate flower's (Punica granatum L.) extract not significantly effecting on growth inhibition of Staphylococcus aureus until 21 days of storage time.Keywords: nutraceutical oral solution of red pomegranate flower's extract, Staphylococcus aureus, the storage time.